5G AND THE FUTURE OF WIRELESS TECHNOLOGIES - Ulasheva Shakhlo Tagaevna; Abraev Azamat Kamoliddinovich; Khuzhamurotova Mashhura Gairat Kizi; Sayfullaev Shahzod Oybek ugli (Journals Park Publishing, 2024)
The fifth generation of mobile networks, or 5G, promises to be one of the most significant technological breakthroughs in communications and wireless technology. With the introduction of 5G, the world will see not only a significant increase in data transfer rates, but also the emergence of new opportunities for various sectors of the economy. In this article, we take a look at what 5G is, how it works, the benefits and challenges it brings, and how it will affect the future of wireless technology.
Keywords: 5G technology, mobile network, wireless technologies, internet of things.